Japanese researcher on Vietnam’s old churches / PV - PV
More than a decade ago, Tomoharu Katano, a Japanese, conducted research on more than 1,200 old churches in northern Vietnam, hoping that the Vietnamese involved would better comprehend the value of the ancient structures to come up with appropriate preservation